Environmental disclosure & financial performance: an empirical study of Malaysia, Thailand and Singapore / Shariful Amran Abd. Rahman … [et al.] - Abd. Rahman, Shariful Amran; Hj. Yusoff, Ruslaina; Wan Mohamed, Wan Nazihah; Abd. Rahman, Samsuria (2008)
This study was carried out to examine the relationship between environmental disclosure and financial performance among the companies in Malaysia, Singapore and Thailand that voluntarily disclose environmental information in their financial report. Two hundred and fifty (250) companies listed in Bursa Malaysia, Singapore Stock Exchange and Thailand Stock Exchange has been identified as samples in the current study. From the total of 250 companies selected, 56 companies are from Malaysia, 37 companies from Thailand and 15 companies from Singapore have been identified as environmental reporting companies. The study hypothesizes that high performance companies have a higher tendency of having formal environmental disclosure in their environmental disclosure. However, the result shows that the performance of the company has no bearing on the decision whether to produce a formal or non-formal environmental disclosure.